Terraforming Mars is not out of the question yet - and microscopic algae could help - Iv. Vasileva; A. Ivanova; S. Alexandrov (Trakia Journal of Sciences)
Recently some researchers have gathered around the claim that the likelihood for terraformation of Mars is slim, either because human technology is not up to the task, or the planet does not posses all the necessary resources to allow the process to be completed successfully. This manuscript takes a closer look both at the latest and previous scientific articles, optimistic and skeptical, while trying to reassess the terraforming potential of the planet. To achieve that, we summarized results from different experiments conducted with algae and higher plants. According to our reevaluation, it is concluded that even if the skeptical papers are right, and the others are overly optimistic, partial terraformation of Mars is still possible. It is also suggested that terraforming the planet partially could be a good option if we want to protect the local organisms, assuming that they exist.